Functions Characterizing the Ground State of the XXZ Spin-1/2 Chain in the Thermodynamic Limit - Dugave, M.; Göhmann, F.; Kozlowski, K.K. (Symmetry, Integrability and Geometry: Methods and Applications, 2014)
We establish several properties of the solutions to the linear integral equations describing the infinite volume properties of the XXZ spin-1/2 chain in the disordered regime. In particular, we obtain lower and upper bounds for the dressed energy, dressed charge and density of Bethe roots. Furthermore, we establish that given a fixed external magnetic field (or a fixed magnetization) there exists a unique value of the boundary of the Fermi zone.